2017
DOI: 10.1007/s00432-017-2391-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of dermoscopy and reflectance confocal microscopy for the diagnosis of malignant skin tumours: a meta-analysis

Abstract: When compared with dermoscopy, RCM has a significantly greater diagnostic specificity for malignant skin tumours and so could improve their detection rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 42 publications
1
21
0
1
Order By: Relevance
“…Our results are consistent with those of previous studies on the diagnostic accuracy of RCM for skin neoplasms in general; a recent meta‐analysis showed a considerably better diagnostic specificity for malignant skin tumors with RCM than for dermoscopy . The pooled sensitivity of dermoscopy for malignant skin tumors was similar to that of RCM (88.1 % vs 93.5 %), but the specificity of dermoscopy was significantly lower than that of RCM (52.9 % vs 80.3 %).…”
Section: Discussionsupporting
confidence: 91%
“…Our results are consistent with those of previous studies on the diagnostic accuracy of RCM for skin neoplasms in general; a recent meta‐analysis showed a considerably better diagnostic specificity for malignant skin tumors with RCM than for dermoscopy . The pooled sensitivity of dermoscopy for malignant skin tumors was similar to that of RCM (88.1 % vs 93.5 %), but the specificity of dermoscopy was significantly lower than that of RCM (52.9 % vs 80.3 %).…”
Section: Discussionsupporting
confidence: 91%
“…RCM imaging has been shown to significantly improve diagnostic accuracy and early detection of melanocytic and nonmelanocytic skin cancers compared with clinical and dermoscopic examination alone. 15 , 16 , 17 , 18 , 19 , 20 A recent meta-analysis that evaluated 21 studies with a total of 3602 lesions found that the pooled sensitivity and specificity was 93.6% (92%-95%) and 82.7% (81%-84%), respectively, for all skin cancers. 16 Particularly, RCM had a sensitivity of 92.7% (90%-95%) and specificity of 78.3% (76%-81%) for detecting melanoma and a sensitivity of 91.7% (87%-95%) and specificity of 91.3% (94%-96%) for detecting basal cell carcinoma.…”
Section: Practicality For Using Confocal In a Practicementioning
confidence: 99%
“…Unsere Ergebnisse stehen im Einklang mit Ergebnissen vorangegangener Studien über die allgemeine diagnostische Genauigkeit der RCM bei Hautneoplasien; eine rezente Metaanalyse zeigte im Vergleich zur Dermatoskopie eine beträchtliche Verbesserung der diagnostischen Spezifität bei malignen Hauttumoren durch die RCM . Die gepoolte Sensitivität der Dermatoskopie für maligne Hauttumoren war ähnlich der der RCM (88,1 % vs. 93,5 %), die Spezifität der Dermatoskopie war aber deutlich niedriger (52,9 % vs. 80,3 %).…”
Section: Diskussionunclassified